A measurement of alpha(s) from the scaling violation in e(+)e(-) annihilation - Abreu, P; Adam, W; Adye, T; Ajinenko, I; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; Andreazza, A; Andrieux, M; et al. (1997)
The hadronic fragmentation functions of the various quark flavours and of gluons are measured in a study of the inclusive hadron production from Z0 decays with the DELPHI detector and are compared with the fragmentation functions measured elsewhere at energies between 14 GeV and 91 GeV. A large scaling violation is observed, which is used to extract the strong coupling constant from a fit using a numerical integration of the second order DGLAP evolution equations. The result is αs(Mz) = 0.1241+0.006-0.007(exp) ±0.009(theory) where the first error represents the experimental uncertainty and the second error is due to the factorization and renormalization scale dependence. © 1997 Elsevier Science B.V.